Noise in accounting information: the signal detection theory perspective - Lau, Yeng Wai (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
Accounting information constitutes a “noisy” representation of economic reality due to the spectrum of accounting alternatives available to meet a diversity of information needs. In the presence of noise, decision-makers can either overlook signals that truly require attention or mistake noise for signals. This paper seeks to (1) discuss how decision-makers fare in discriminating accounting signals from noise based on extant empirical findings, (2) highlight the adverse effects of noise in accounting information from the signal detection theory perspective, and (3) offer recommendations on how best to fend of the adverse influence of noise.